Clinical effect of intravenous ciprofloxacin on hospital-acquired pneumonia - Okimoto, Niro; Yamato, Kenji; Honda, Yoshihiro; Kurihara, Takeyuki; Osaki, Kohichi; Asaoka, Naoko; Fujita, Kazue; Ohba, Hideo (Journal of infection and chemotherapy : official journal of the Japan Society of Chemotherapy, 2005)
The effect of intravenous ciprofloxacin (CPFX) on hospital-acquired pneumonia was examined. The subjects were 32 patients with hospital-acquired pneumonia classified as being in group I, group II, and group III, based on The Japanese Respiratory Society Guidelines for management of hospital-acquired pneumonia. None of the patients had received antibiotic treatment for the pneumonia. CPFX 300mg was intravenously infused twice daily for 3–14 days, and its clinical effect, bacterological effect, and side effects were examined. Intravenous CPEX was clinically effective in 21 of the 32 patients, with an efficacy rate of 65.6%. With regard to bacteriological efficacy, 4 of 5 strains of methicillin-sensitive Staphylococcus aureus, 2 of 3 strains of Klebsiella pneumoniae, 1 of 2 strains of Streptococcus pneumoniae, 1 of 2 strains of Streptococcus agalactiae, 1 of 2 strains of Pseudomonas aeruginosa, 1 of 2 strains of Serratia marcescens, and the 1 strain of Klebsiella oxytoca were eradicated, with an eradication rate of 42.3% (11 of 26 strains whose fate was confirmed eradicated). Abnormal laboratory findings (side effects) were observed in 11 of the 32 patients (34.4%), but all side effects were mild. Based on the above data, intravenous CPFX may be the drug which should be recommended as the first choice for hospitalacquired pneumonia.